Weight Suppression in Bulimia Nervosa: Associations with Biology and Behavior - Bodell, Lindsay P. (J Abnorm Psychol, 2015)
Bulimia nervosa (BN) is a serious eating disorder that can persist for years and contribute to medical complications and increased mortality, underscoring the need to better understand factors maintaining this disorder. Higher levels of weight suppression (WS) have been found to predict both the onset and maintenance of BN; however, no studies have examined mechanisms that may account for the effects of WS on BN. We hypothesized that high WS would lead to reduced leptin levels, which may increase risk of binge eating by modulating reward responses to food. The current study examined the relationship between WS, leptin levels, and the reinforcing value of food in women with BN (n=32) and non-eating disorder controls (n=30). Participants provided information on WS, completed a fasting blood draw to obtain serum leptin, and completed a progressive ratio task to measure the reinforcing value of food. Individuals with BN had greater WS (p<.01) and reinforcing food value (p<.05) compared to controls. Additionally, higher WS was associated with both lower leptin (p<.05) and increased reinforcing value of food (p<.05). Contrary to hypotheses, BN and control participants did not differ significantly on leptin levels, and leptin levels were not significantly associated with the reinforcing value of food. Findings support that efforts to conform to the thin ideal may alter drive to consume rewarding foods and leave women vulnerable to binge episodes. However, mechanisms through which WS contributes to food reward and binge eating remain unknown.